Performance improvement of pilot‐assisted power allocation in vehicular small cells with preprocessing under measurement errors. Issue 4 (1st July 2018) - Alizadeh, Sajjad; Saadat, Reza
Abstract : The authors consider the pilot‐assisted power allocation of the wireless backhaul link presented in some recent literatures in the vehicular heterogeneous small cell networks under the imperfect measurement. To implement aforementioned algorithm, it is essential to measure the received power on the backhaul link. However, due to the dynamic feature of the wireless backhaul in the vehicular small cells, the perfect measurement is approximately impossible in practice. Moreover, in spite of the signal‐to‐interference plus noise ratio (SINR) balancing property, the pilot‐assisted algorithm is significantly sensitive to the measurement error. Accordingly, in this study at first the authors formulate the measurement error of the uplink received power in the macro base stations and then propose a preprocessing‐based algorithm to reduce the effects of the imperfect measurement on the SINR balancing of the pilot‐based algorithm. Specifically, in two‐layer small cell network considered in this work, the authors derive a modification coefficient proportional to the maximum percentage of the measurement error in a layer by solving an optimisation problem and utilise it in another layer before transmission. Simulation results demonstrate the effectiveness of the proposed scheme in comparison with the existing algorithm in terms of the SINR balancing especially in high measurement error.